Unique and contrasting effects of light and temperature cues on plant transcriptional programs. Issue 3 (7th August 2020) - Jarad, Mai; Antoniou-Kourounioti, Rea; Hepworth, Jo; Qüesta, Julia I.
ABSTRACT: Plants have adapted to tolerate and survive constantly changing environmental conditions by reprogramming gene expression in response to stress or to drive developmental transitions. Among the many signals that plants perceive, light and temperature are of particular interest due to their intensely fluctuating nature which is combined with a long-term seasonal trend. Whereas specific receptors are key in the light-sensing mechanism, the identity of plant thermosensors for high and low temperatures remains far from fully addressed. This review aims at discussing common as well as divergent characteristics of gene expression regulation in plants, controlled by light and temperature. Light and temperature signaling control the abundance of specific transcription factors, as well as the dynamics of co-transcriptional processes such as RNA polymerase elongation rate and alternative splicing patterns. Additionally, sensing both types of cues modulates gene expression by altering the chromatin landscape and through the induction of long non-coding RNAs (lncRNAs). However, while light sensing is channeled through dedicated receptors, temperature can broadly affect chemical reactions inside plant cells. Thus, direct thermal modifications of the transcriptional machinery add another level of complexity to plant transcriptional regulation. Besides the rapid transcriptome changes that follow perception of environmental signals, plant developmental transitions and acquisition of stress tolerance depend on long-term maintenance of transcriptional states (active or silenced genes). Thus, the rapid transcriptional response to the signal (Phase I) can be distinguished from the long-term memory of the acquired transcriptional state (Phase II – remembering the signal). In this review we discuss recent advances in light and temperature signal perception, integration and memory in Arabidopsis thaliana, focusing on transcriptional regulation and highlighting the contrasting and unique features of each type of cue in the process.